2013
DOI: 10.1186/1742-2094-10-112
|View full text |Cite
|
Sign up to set email alerts
|

Different TLR4 expression and microglia/macrophage activation induced by hemorrhage in the rat spinal cord after compressive injury

Abstract: BackgroundHemorrhage is a direct consequence of traumatic injury to the central nervous system and may cause innate immune reactions including cerebral Toll-like receptor (TLR) 4 upregulation which usually leads to poor outcome in the traumatic brain injury. In spinal cord injury (SCI), however, how hemorrhage induces innate immune reaction in spinal parenchyma remains unknown. The present study aimed to see whether blood component and/or other factor(s) induce TLR4 and microglia/macrophages involved innate im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 44 publications
2
44
0
Order By: Relevance
“…Consistent with our study, Freitas et al showed that increased macrophage and neutrophil infiltration was found in the WT mice [37]. Zhang et al reported that the hematoma in the injury site would up-regulate TLR4 and activate macrophages after injury, which further initiated pro-inflammation cascade, indicating that TLR4 plays a positive role in inflammatory responses [38]. In our study, compared with the I/R groups, T lymphocytes, CD4 + and CD8 + T cells, and monocyte/macrophages, were increased markedly in the HMGB1 group.…”
Section: Discussionsupporting
confidence: 78%
“…Consistent with our study, Freitas et al showed that increased macrophage and neutrophil infiltration was found in the WT mice [37]. Zhang et al reported that the hematoma in the injury site would up-regulate TLR4 and activate macrophages after injury, which further initiated pro-inflammation cascade, indicating that TLR4 plays a positive role in inflammatory responses [38]. In our study, compared with the I/R groups, T lymphocytes, CD4 + and CD8 + T cells, and monocyte/macrophages, were increased markedly in the HMGB1 group.…”
Section: Discussionsupporting
confidence: 78%
“…More topical studies also suggest a protective and Bpositive^regulatory function. After SCI, microglia plays a decisive role in secondary injury, and the activation of a single macrophage phenotype can facilitate proper wound healing following SCI [15]. Successful orchestration of macrophage-mediated tissue repair requires fine tuning different macrophage phenotypes to harmoniously facilitate transitions among different wound healing phases [22].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, microgliosis was observed by SDF-1a. After SCI, microglia which are decisive regulators of tissue damage after SCI accumulate within the epicenter and the hematoma of the injured spinal cord and are a putative source of IL-1b [15].…”
Section: Introductionmentioning
confidence: 99%
“…Of the nine TLRs, protein expression has been demonstrated for TLR2, 3, 4, 6, 7 and 9 in primary microglia culture from mouse brain and TLR 1 -4 from human brain (Olson and Miller, 2004;Yoon et al, 2008) (Table 2). In vivo, the expression levels of microglial TLRs seem to be kept low under normal conditions (Bsibsi et al, 2002;Casula et al, 2011;Shi et al, 2011;Zhang et al, 2013;Zhao et al, 2015). However, the upregulation of TLR2, 3 or 4 has been reported in the brain from a mouse model of Alzheimer's disease (AD) and in the spinal cord sections from a mouse model of spinal cord injury , as well as amyotrophic lateral sclerosis (ALS) patients (Casula et al, 2011) and multiple sclerosis (MS) patients (Bsibsi et al, 2002), suggesting the potential of microglial TLRs to participate in neuro-immune communication in the CNS.…”
Section: Expression Of Tlrs In Microgliamentioning
confidence: 98%